O Aleph e seus duplos: mimesis e auto-reflexividade na obra de Jorge Luis Borges - Torres, José Wanderson Lima (2012)
This study approach the Jorge Luis Borges s prose of fiction under the perspective of mimesis and the self-reflexivity. The hypothesis is that the Aleph is a central symbol of the Borges s fictional universe. The rewriting and the retake of this symbol along of his work entail to a reflection about the possibilities and the limits of mimesis. This study is divided in three parts which contain two chapters. The first part Bibliographic revision and conceptual fundaments of inquiry discuss the critical fortune of author (Chapter 1) and the concepts that will give sustentation to the inquiry (Chapter 2). The second part About the Borges s aesthetic project sketch out the literary project defended by Borges that is his conception of the literature and his ideological matrix (Chapter 3) beside his anti-psychologism and his nostalgia of epos (Chapter 4). The third and last part is entitled The Aleph and his doubles. In the chapter 5 this study analyses the short story El Aleph and consider its centrality on the Borges s work. The argument that is on this short story Borges elaborates a reflection about mimesis. In the chapter 6, on the same hand, four short stories will be analysed: Funes el memorioso ; El Libro de Arena ; El evangelio según Marcos and Del rigor en la ciencia . The conclusion that is the Borges s literature is self-awake of its process as such demonstrate its parodic sense and its bookish origin. Hence, the Borges s literature overlapping the mimetic crisis of language and challenge the limits between fiction and reality. However, it doesn t surrender to the nihilist perspective that is closing of literature to the world